Workplace accident risk analysis using the bowtie method in the construction industry: a literature review - Fajrisa, Deva; Hariyono, Widodo; Sulistyawati, Sulistyawati (Jurnal EduHealth, 2024)
Occupational Health and Safety (OHS) is an important aspect of decent work, with work accident statistics assessing worker protection from hazards and risks. The construction industry, which has a high risk of accidents, requires effective risk management, including bowtie analysis. This research analyzes the use of the bowtie method in the construction industry in Indonesia. A systematic review with a PRISMA approach was conducted. Relevant articles were searched during the period 2018-2023 through Sinta, Google Scholar, and PubMed using predefined inclusion and exclusion criteria, namely "bowtie method" and "Bow tie Analysis in Indonesia." Out of 18 articles identified with the specified keywords, quality evaluation resulted in six selected articles that met the criteria. The research findings encompass various risks such as the collapse of girder beams and accidents related to COVID-19. The impacts involve various levels of injuries up to fatalities, with mitigation efforts including the use of Personal Protective Equipment (PPE) and operator supervision. Analysis of the findings through tables and diagrams presents consistently emerging common risks. Detailed findings on the highest risks, namely girder collapse and workers falling from heights, provide a comprehensive overview of threats, consequences, and mitigation efforts